Violet Holmes and the Agents of H.I.V.E: Adventure of a Teenage Detective - Nicko Vaughan (Orange Pip Books, 2020)
The world-famous detective, Sherlock Holmes, raised a baby girl after her mother exploded. Now a young woman, she's starting a new school, which is always difficult, especially if you suspect the teaches of being part of a crime ring. Can Violet Holmes and her new-found friends solve this mystery?